2021
DOI: 10.1155/2021/6610726
|View full text |Cite
|
Sign up to set email alerts
|

Furazolidone Increases Survival of Mice Exposed to Lethal Total Body Irradiation through the Antiapoptosis and Antiautophagy Mechanism

Abstract: Exposure to total body irradiation (TBI) causes dose- and tissue-specific lethality. However, there are few effective and nontoxic radiation countermeasures for the radiation injury. In the current study, mice were pretreated with a traditional antimicrobial agent, FZD, before TBI; the protective effects of FZD on radiation injury were evaluated by using parameters such as the spleen index and thymus index, immunohistochemical staining of intestinal tissue, and frequency of micronuclei in polychromatophilic er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Aspirin ameliorates radiation-induced kidney and lung damage and reduces post-irradiation chromosomal aberrations [ 286 ]. A recent meta-analysis of randomized controlled trials indicates that acetylsalicylic acid reduces the overall risk of recurrence and mortality of colorectal cancer and/or colorectal adenomas, which increases the interest in its possible use as a radioprotector/radiosensitizer [ 287 ]. Flurbiprofen showed radioprotection in clinical studies, e.g., delaying the onset of mucositis and reducing its severity after radiotherapy in head and neck cancer patients, although the overall severity or duration of mucositis was not improved [ 288 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Aspirin ameliorates radiation-induced kidney and lung damage and reduces post-irradiation chromosomal aberrations [ 286 ]. A recent meta-analysis of randomized controlled trials indicates that acetylsalicylic acid reduces the overall risk of recurrence and mortality of colorectal cancer and/or colorectal adenomas, which increases the interest in its possible use as a radioprotector/radiosensitizer [ 287 ]. Flurbiprofen showed radioprotection in clinical studies, e.g., delaying the onset of mucositis and reducing its severity after radiotherapy in head and neck cancer patients, although the overall severity or duration of mucositis was not improved [ 288 ].…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Mice were weighed daily throughout the experiment. On the last day of the investigation, mice were placed in a closed environment, and fecal samples were taken for 3 h. Next, disease activity index (DAI), fecal water content, and loose stool rate were determined as described previously (Han et al, 2019; Ma et al, 2021a; Yang et al, 2022; Zhan et al, 2022). Mice were anesthetized with 20% chloral hydrate, and the myeloperoxidase (MPO) activity in extracted colon tissue was assessed based on the requirements of a specific kit.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, FZD treatment reduced unstable chromosomal aberrations (CAs) (such as acentric and dicentric chromosomes (DC)), chromosome breaks, and radiosensitivity of intestinal epithelial cells. Ma et al [25] showed that FZD treatment significantly improved the sur-vival of lethal dose-irradiated mice, decreased the number of micronuclei (MN), increased the number of leukocytes and immune organ indices, and reversed the apoptosis and autophagy in the small intestine, thus restoring intestinal integrity. Their experiments showed that irradiation resulted in villous shortening and crypt dilation accompanied by epithelial atrophy or slough, and even marked edema and inflammatory cell infiltration, and how FZD significantly induced damage recovery.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Flurbiprofen also showed radioprotection in clinical studies, e.g., delaying the onset of mucositis and reducing its severity after RT in 12 head and neck cancer patients, although the overall severity or duration of mucositis was not improved [138]. A recent meta-analysis of randomized controlled trials indicates that aspirin reduces the overall risk of recurrence and mortality of colorectal cancer and/or colorectal adenomas, which increases the interest in its possible use as a radiomitigator [24,25]. However, nonselective COXi are known to cause undesirable side effects including GI ulcers and bleeding when taken for continued periods of time.…”
Section: Nonsteroidal (Nsaids) and Steroidal Anti-inflammatory Radiom...mentioning
confidence: 99%